Brincando com as cores - Rios, Agda Rodrigues; Xavier, Eliene; Oliveira, Maria de Fatima; Santana, Marli Felício; Botassim, Rosa Maria Ferreira; Pereira, Valdirene Alves (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf